Analisis Pendapatan dan Kelayakan Usahatani Rumput Laut Berdasarkan Skala Usaha di Desa Bakealu Kecamatan Wakorumba Selatan Kabupaten Muna - H, Husdila; B, Bahari; W, Weka (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to (1) 1. Analyze the scale of seaweed farming businesses in Bakealu Village, South Wakorumba District, Muna Regency., 2) Analyze the Cost Structure of Seaweed Farming Based on business scale in Bakealu Village, South Wakorumba District, Muna Regency. 3) Analyze the income and feasibility of seaweed farmers based on the scale of farming in Bakealu Village, South Wakorumba District, Muna Regency. The population in this research is Seaweed farmers in Bakealu Village, South Wakorumba District, 60 families. Determining the research sample was carried out using the census sampling technique method because all members of the pupulation were sampled, where the total population was 30 seaweed farmers, so the total number of respondents was 30 people. Data analysis uses revenue, income and R/C ratio analysis. The research results show that income in this research is grouped based on the business scale that has been determined. scale I income is IDR 28.421.988, scale II income is IDR 14.959.668, and scale III income is IDR 13.367.201.